New works for different places : TSWA four cities project : Derry, Glasgow, Newcastle, Plymouth. - TSWA (Bristol : TSW - Television South West and South West Arts, 1990)
Adams, Dennis ; Barry, Judith ; Brisley, Stuart ; Burden, Chris ; Cadieux, Genevieve ; Chadwick, Helen ; Counsell, Melanie ; Deacon, Richard ; Emery, Janette ; Rowbotham, Kevin ; Fischli & Weiss ; Gec, Stefan ; Hamilton Finlay, Ian ; Haselden, Ron ; Hatoum, Mona ; Jaffe, Lee ; Jetelova, Magdalena ; Kabakov, Ilya ; McIver, Moira ; Meireles, Cildo ; Phoaphanit, Vong ; Rodney, Donald ; Spero, Nancy ; Sterbak, Jana ; Trockel, Rosemarie ; Viner, Darrell ; Wilson, Richard
New works for different places : TSWA four cities project : Derry, Glasgow, Newcastle, Plymouth, Orchard Gallery, Derry ; Third Eye Centre, Glasgow ; Projects UK, Newcastle ; Plymouth ARts Centre, 1990
boek
Keywords: Derry; Glasgow; Newcastle; Plymouth